The prognostic effect of the systemic immune-inflammation index on overall survival of periampullary cancer - Yur, Mesut; Balin, Safak Ozer; Aygen, Erhan; Ilhan, Yavuz Selim; Yilmaz, Serkan; Ebiloglu, Mehmet Fatih (Taylor & Francis Ltd, 2023)
ObjectiveThe systemic immune-inflammation index (SII) is used to assess survival in many cancers. SII has been examined separately in pancreatic head, ampulla, and distal choledochus cancers, and different cut-off values were found. Detecting the location of periampullary cancer before surgery may be difficult or misleading. This study aimed to investigate the use of SII in predicting overall survival (OS) with periampullary cancers regardless of tumor location.MethodsBetween January 2010 and January 2020, 163 patients who underwent pancreaticoduodenectomy for periampullary tumors were assessed. After applying the exclusion criteria, data from 116 patients with cancer who underwent pancreaticoduodenectomy were included in the study.ResultsOS was compared using Kaplan-Meier curves. The prognostic significance of baseline SII and other factors were assessed in univariate and multivariate analyses using the Cox proportional hazard regression model. Univariate analysis demonstrated that age & GE;60.5 years (hazard ratio [HR]: 2.042, 95% CI: [1.355-3.078]; p = 0.001), male sex (HR: 1.863, 95% CI: [1.231-2.821]; p = 0.003), tumor in the pancreatic head vs. ampulla (HR: 2.150, 95% CI: [1.364-3.389]; p = 0.001), tumor in the pancreatic head vs. distal choledochus (HR: 1.945, 95% CI: [1.091-3.472]; p = 0.024), N (+) stage (HR: 1.868, 95% CI: [1.223-2.854]; p = 0.004), total bilirubin level >0.35 (HR: 2.131, 95% CI: [1.245-3.649]; p = 0.006), NLR >2.13 (HR: 1.911, 95% CI: [1.248-2.925]; p = 0.003), and SII >704 (HR: 1.966, 95% CI: [1.310-2.950]; p = 0.001) were significantly associated with OS. Multivariate analysis revealed that SII >704 (HR: 2.375; p < 0.001), age & GE; 60.5 years (HR: 2.728; p < 0.001), N-stage positivity (HR: 3.431; p < 0.001), and tumor in the pancreatic head vs. ampulla (HR: 2.801; p < 0.001) were independently associated with poor survival. There was no difference between tumor locations in terms of SII (p = 0.206).ConclusionsSII is an independent prognostic risk factor and may be a marker for predicting OS in patients with periampullary cancer. There was no statistical difference between the tumor locations in terms of SII. A single cut-off value of SII may be used for periampullary cancer survival without the need for a pathology specimen.
Keywords: Periampullary cancer; pancreas; distal choledochus; ampulla; systemic immune-inflammation index; neutrophil-to-lymphocyte ratio